Nanoparticle Drug Delivery System - Afinasari, Auliya; Amalia, Eri (Indonesian Journal of Pharmaceutics, 2022)
Drug Delivery System is a method of drug formulation, which aims to deliver the active substance to achieve a therapeutic effect in the body. Along with the development of science in the field of drug manufacturing technology, drug delivery systems have evolved from conventional to targeted delivery systems and even nanorobots, gene therapy, biological products, and long-term delivery systems.Among the drug delivery systems that have been developed, nanotechnology has been applied as a targeted delivery system such as in cancer treatment. This review is focused on nanotechnology especially in nanoparticle dosage forms, including liposomes, dendrimers, niosomes, micelles, solid-lipid nanoparticles, nanospheres, nanocapsules, and gold nanoparticles. The data were collected from 41 primary published journals and 20 supporting literatures. The basic principles, strategies, and carrier systems used in the manufacture of each preparation will be presented in this article, including prospects in the future for SOPs.